2006
DOI: 10.1002/esp.1336
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the cosmogenic nuclide production topographic shielding scaling factor for large areas using DEMs

Abstract: The recent surge of applications using terrestrial cosmogenic nuclides (TCNs) to calculate catchment-averaged erosion rates from isotopic concentrations in fluvial sediment, and the prospect of coupling TCN production functions with numerical surface process models (SPMs), necessitate a fast and accurate algorithm for the calculation of topographic shielding. Topographic shielding refers to the proportion of the incoming cosmic radiation that is shielded by the surrounding topography, the scaling factor being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 24 publications
(28 reference statements)
0
110
0
Order By: Relevance
“…We adopt the method of Codilean (2006), in which both the effect of dipping sample surfaces and shielding by topography blocking incoming cosmic rays are computed. The Codilean (2006) method is spatially distributed: each pixel in a digital elevation model (DEM) has its own topographic shielding correction that varies from 0 (completely shielded) to 1 (no topographic shielding). These correction values are calculated by modeling shadows cast upon each pixel in the DEM from every point in the sky.…”
Section: Topographic Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt the method of Codilean (2006), in which both the effect of dipping sample surfaces and shielding by topography blocking incoming cosmic rays are computed. The Codilean (2006) method is spatially distributed: each pixel in a digital elevation model (DEM) has its own topographic shielding correction that varies from 0 (completely shielded) to 1 (no topographic shielding). These correction values are calculated by modeling shadows cast upon each pixel in the DEM from every point in the sky.…”
Section: Topographic Shieldingmentioning
confidence: 99%
“…These again are spatially distributed and so authors reporting catchmentaveraged denudation rates frequently report averaged shielding values. Although software packages do exist for calculating spatially averaged topographic shielding (e.g., Codilean, 2006) and snow shielding (e.g., Schildgen et al, 2005), results from these models are not integrated with spatially varying production rates. Finally, in landslide dominated terrain, removal of thick layers of sediment can dilute cosmogenic nuclide concentrations in river sediment (Niemi et al, 2005;Yanites et al, 2009;West et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While this is an attractive theory, we believe that it is too simplistic, and that the calculation of basin-averaged shielding factors is necessary. Basin-averaged shielding factors are calculated from DEMs (Codilean, 2006), digital representations of ground surface topography or terrain. The most common structure for a DEM is a regular array of squares of equal size, and hence equal area.…”
Section: Resultsmentioning
confidence: 99%
“…This in contrast to the alternative method of using relief-shadow modelling to account for topographic shielding. Codilean (2006) found that both methods produce similar results. An algorithm was developed that calculates the elevation angle for each grid cell within the drainage basin to every other cell of the digital elevation model for each 5° azimuth bin.…”
Section: Topographic Shieldingmentioning
confidence: 88%
See 1 more Smart Citation